(untitled) (Third Sector Social Economic Review, 2017)
Nowadays, it is an inevitable requirement to enhance the level of technology in production as well as the added value in order to enable individuals constituting the society and the society as a whole to live in a sustainable welfare. It is only possible for the Republic of Turkey to reach the target of export worth of 500 billion dollars and the figure of 25 thousand dollars for national income per capita in 2023 through carrying out business having high level of R&D and know-how. For this purpose, as the public authority, Ministry of Science, Industry and Technology of the Republic of Turkey started to implement Techno-Initiative Capital Support (TICS) program in 2009 in order to ensure that Turkey becomes a country which “produces and sells its own technology” rather than being a country which buys and uses the technology. The grant program which aimed to attract young entrepreneurs’ attention, to create a change in behaviour towards “developing technology-based business ideas”, and to ensure that this change in behaviour is sustainable, was considered to be a social marketing application by the researchers since the program promotes early-stage entrepreneurs who were chosen as target audience to show the desired behaviour voluntarily so that they can be useful to themselves but also to the society which they are a member of. Therefore, this study investigated how elements of social marketing mix can be adapted to the planning process of TICS grant program which is an application for improvement of societal and individual welfare, and it is believed that this study will greatly contribute to the related literature since it is one of the few studies on social marketing in our country.